Numerical study of phase change material based orthotropic heat sink for thermal management of electronics components. (December 2016) - Sahoo, Santosh Kumar; Rath, Prasenjit; Das, Mihir Kumar
Highlights: Effect of orthotropicity of fin in lowering the base temperature of heat sink and also its effect on melt fraction of PCM. Effect of orthotropicity in minimizing the temperature gradient along the axial direction of the fin. Comparison of the thermal performance of heat sink with orthotropic and isotropic fins. Orthotropic heat sink reduces the weight burden on the cooling system compared to isotropic one. Abstract: The benefits of orthotropic composite fins as the thermal conductivity enhancer in the design of phase change material (PCM) based heat sink are investigated. Composite fins reduce the system's overall weight as well as improve its thermal performance. A numerical model is developed considering conduction and natural convection in the liquid phase and pure conduction in the solid phase of PCM. Conduction in the fin region assumed orthotropic. The orthotropicity is modeled by adding a departure source term in the isotropic heat conduction. The finite volume method is used to discretize the governing mass, momentum and energy transport equations. The enthalpy porosity method is used to model the phase change in PCM. The Semi Implicit Pressure Linked Equation Revised (SIMPLER) algorithm is used to solve the flow field in liquid PCM region. The line-by-line TDMA is used to solve the resulting set of discrete algebraic equations. In order to reduce computational time, a symmetry section is considered in the present study. It is found that orthotropic fins gives better performance in reducing the base temperature compared to isotropic fins. Orthotropic fins of less volume can replace the isotropic fins of more volume. Also, uses of orthotropic fins under higher heat fluxes give better performance in comparison to isotropic fins. In addition, the numerical results show the effect of the Stefan number, the Rayleigh number and the Prandtl number on transient performance of orthotropic heat sink. Therefore, the use of orthotropic fins instead of isotropic one reduces the thermal constraint as well as weight burden on the electronic components.